WACANA MARANTAU DALAM DENDANG BUJANG MARANTAU - Nofer, Dolly (Paraguna, 2021)
The existence of a significant dendang (song) in the musical art of Saluang Darek. Apart from being a musical medium, dendang plays an important role in conveying messages verbally. This research is a study of the discourse of marantau (migration) in the dendang 'Bujang Marantau'. The significance of the study of the discourse is based on a thought that dendang as a work of art contains certain values, ideas, and thoughts related to life experiences in everyday life which are often not revealed on the surface. The disclosure of the marantau discourse in the song uses perspective and discourse analysis, with interpretive qualitative methods. After the translation of the 'Bujang Marantau' dendang text, the text is then interpreted to include other texts other than the dendang which include; creator (Sawir Sutan Mudo), Saluang Darek music, Minangkabau culture, and the marantau tradition. The texts outside the 'Bujang Marantau' dendang are the surrounding context. The whole meaning of the discourse of marantau in the dendang 'Bujang Marantau' can be understood through the disclosure of the relation of meaning between the text and the context. Based on the studies that have been carried out, it was found that the discourse of marantau in the dendang 'Bujang Marantau' is a dilemmatic fact that occurs in the marantau tradition. Marantau activities apparently not only have an impact on economic improvement, self-maturation, but simultaneously trigger suffering.